Case Report: Pancreatic Neuroendocrine Tumor With Liver Metastasis and Portal Vein Thrombosis - Tian, Yulong; Qi, Xingshun; Aljbri, Afaf; Xu, Ke; Zhong, Hongshan (Frontiers in Oncology, 2022)
Introduction: Pancreatic neuroendocrine neoplasms (PNENs) are a rare pancreatic tumor originating from pancreatic neuroendocrine cells. There is no consensus on the treatment for PNENs with unresectable liver metastases. Transcatheter arterial chemoembolization（TACE）is the preferred treatment for unresectable primary liver cancer. But the efficacy of TACE and anticoagulation in PNENs with unresectable liver metastases and portal vein thrombosis has never been reported. Methods and results: We present the case of a 50-year-old male patient with hepatitis C was found to have a single liver mass during a regular physical examination in 2016. The liver mass was surgically removed. Postoperative pathology suggested neuroendocrine tumor of the liver, and it was suggested to look for the primary tumor. The patient was followed up until 2020, and the primary pancreatic tumor was found, along with multiple liver metastases, portal vein thrombosis. After transcatheter arterial embolization, anticoagulation and endocrine therapy, the patient's tumor load was relieved and the portal vein was recanalized. Conclusion: The article reports the disease course in a case of functional pancreatic neuroendocrine tumor with liver metastasis and portal vein thrombosis, and reviews previous literature. To our knowledge, we reported for the first time the efficacy of TACE and anticoagulation in PNENs with unresectable liver metastases and portal vein thrombosis.